2011
DOI: 10.2214/ajr.10.5221
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension in Patients With Bronchiectasis: Prognostic Significance of CT Signs

Abstract: Pulmonary hypertension, reflected by pulmonary arterial enlargement on CT scans, is a highly significant prognostic indicator in the evaluation of patients with bronchiectasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 21 publications
1
42
0
Order By: Relevance
“…We add that associated COPD might play a pivotal role in predicting mortality, but further research with larger populations is needed. Although PH is a known risk factor for mortality and the percentages of deaths were higher in the patients with PH (42%) versus without PH (28%), there was no significant difference in terms of mortality [34]. This might be hampered by the lack of echocardiographic data in 130 patients.…”
Section: Discussionmentioning
confidence: 98%
“…We add that associated COPD might play a pivotal role in predicting mortality, but further research with larger populations is needed. Although PH is a known risk factor for mortality and the percentages of deaths were higher in the patients with PH (42%) versus without PH (28%), there was no significant difference in terms of mortality [34]. This might be hampered by the lack of echocardiographic data in 130 patients.…”
Section: Discussionmentioning
confidence: 98%
“…(3140) Devaraj and colleagues have recently shown that the right and left pulmonary artery diameters exceeding 1.8 cm are the best predictor of mortality in patients with bronchiectasis; as these CT findings are considered to be a biomarker for elevated PAP. (41) There are some authors that have recently proposed using the ratio of the pulmonary artery diameter to the aortic diameter (PAD/AoD) as a proxy for pulmonary arterial enlargement. (20) The PAD/AoD ratio is limited by many factors not the least of which is the great deal of variability in aortic size which is independent of pulmonary arterial pressures.…”
Section: Non Contrast Ct Findings Of Elevated Papmentioning
confidence: 99%
“…In a study involving 70 individuals with bronchiectasis diagnosed by HRCT, air trapping was observed in 34% of the images obtained during expiration (39) . In the present study, the sample of patient in whom appropriate expiratory HRCT scans were available was small ( n = 10), due to the technical difficulties for the acquisition of examinations of good quality.…”
Section: Discussionmentioning
confidence: 99%